Secure attachment and infant development in vulnerable populations - Ferreyros Peña, Mónica (2017)
There are several cultural, social and personal elements in our country that influence parental behavior and therefore, unable the best development of the infant. This investigation wants to determine the effectiveness of a program directed to mothers of vulnerable populations that encourages a secure attachment bond, to improve the social-emotional and cognitive development of the infant in its first year of life. It is a quantitative research of experimental type and with a qualitative analysis. The results confirm the hypothesis, since the applied program shows a positive impact in each of the developmental dimensions (motor, cognitive, language, socioemotional and self-effort) in the intervention group. Regarding the presence-absence of attachment behaviors, mothers and children in the experimental group show a presence of behaviors of a secure bond attachment to 92.86% and mothers and children in the control group 62.5%.